The thin man [videorecording (DVD)] - Van Dyke, W. S.; Powell, William, 1892-1984; Loy, Myrna, 1905-1993; Hammett, Dashiell, 1894-1961 (Warner Home Video, 2002)
Crime/comedy thriller featuring Nick Charles, private eye, and his wife Nora. The plot unfolds at Christmas when an eccentric inventor disappears after threatening his mistress with a lawsuit for embezzlement.